The Effectiveness of the Example and Non-Example Learning Model Incorporating Horseshoeing Tools on the Third-Grade Elementary School Students’ Learning Interest - Pekei, Manderika; Malihatul Hawa, Anni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
One of the issues discovered in the learning process of third-grade students at SDN Gendangank 03, Ungaran District, Semarang Regency, is the low level of student knowledge, as reflected in the average learning outcomes, which still require improvement. This academic achievement indicates that the learning process has not effectively captured students' interest, largely due to the teacher-centred approach. To address this issue, the researcher proposes the Example and Non-Example learning model supported by Horseshoeing tools to enhance students' learning interest. The t-test results displayed a t-value of 4.987 with a degree of freedom (df) of 54 and a p-value (both one-sided and two-sided) of less than 0.001. This indicates that the difference in learning interest between the two groups is statistically significant at a 95% confidence level. In other words, the Example and Non-Example learning model incorporating the horseshoeing tools is significantly more effective in increasing students' learning interest. The statistical analysis of both groups revealed differences in the average learning interest between the control and experimental groups. The control group consisted of 26 students with an average learning interest score of 74.42, a standard deviation of 9.091, and a standard error mean of 1.783. This suggests that the learning interest within the control group exhibited considerable variability among students.